Critical Response to "A Short History of K-12 Public School Spending in British Columbia" - Laitsch, Dan; Malcolmson, John; Kuehn, Larry (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2022)
In Issue 196 of the Canadian Journal of Educational Administration and Policy (CJEAP), the journal published an article by Jason Ellis, A Short History of K-12 Public School Spending in British Columbia, 1970-2020 that claimed “K-12 public education spending in British Columbia – adjusted for inflation – is 250 percent higher in 2020 than it was in 1970” (Ellis, 2021, p. 102). We illustrate how this claim lacks a theoretical framework, is based on weak data sources, a flawed research method and skewed analysis that results in a misleading understanding of resource allocations in BC. We present alternative ways to understand spending on education in BC in an effort to correct the scholarly and public record.